Antiprotons and Elementary Particles over a Solar Cycle: Results from the Alpha Magnetic Spectrometer - Aguilar, M. (American Physical Society (APS), 2025)
We present results over an 11-year Solar cycle of cosmic antiprotons based on 1.1 ×106 events in the rigidity range from 1.00 to 41.9 GV. The ¯𝑝 fluxes exhibit distinct properties. The magnitude of the ¯𝑝 flux temporal variation is significantly smaller than those of 𝑝, 𝑒−, and 𝑒+. A hysteresis between the ¯𝑝 fluxes and the 𝑝 fluxes is observed, whereas the ¯𝑝 and 𝑒− fluxes show a linear correlation. With a model-independent analysis, we found a universal relation between the shape of the rigidity spectrum and the magnitude of flux temporal variation over an 11-year Solar cycle for both positively and negatively charged particles. The simultaneous results on ¯𝑝 and 𝑝, 𝑒−, and 𝑒+ provide unique information for understanding particle transport in the Solar System as a function of mass, charge, and spectral shape.